Microduplication 10q24.31 in a Spanish girl with scoliosis and myopathy: The critical role of LBX - Fernández-Jaén, Alberto; Suela, Javier; Fernández-Mayoralas, Daniel Martín; Fernández-Perrone, Ana Laura; Wotton, Karl R.; Dietrich, Susanne; Castellanos, Maria del Carmen; Cigudosa, Juan C.; Calleja-Pérez, Beatriz; López-Martín, Sara (American journal of medical genetics. Part A, 2014)
LBX1 plays a cardinal role in neuronal and muscular development in animal models. Its function in humans is unknown; it has been reported as a candidate gene for idiopathic scoliosis. Our goal is to document the first clinical case of a microduplication at 10q24.31 (chr10:102927883‐103053612, hg19), affecting exclusively LBX1. The patient, a 12‐year‐old girl, showed attention problems, dyspraxia, idiopathic congenital scoliosis, and marked hypotrophy of paravertebral muscles. Her paternal aunt had a severe and progressive myopathy with a genetic study that revealed the same duplication. We propose to consider genetic studies, particularly of LBX1, in patients with scoliosis and/or hypotrophy‐hypoplasia of paravertebral muscles of unknown etiology. © 2014 Wiley Periodicals, Inc.